A hybrid CO2 electroreduction system mediated by enzyme-cofactor conjugates coupled with Cu nanoparticle-catalyzed cofactor regeneration. (December 2019) - Song, Haiyan; Ma, Chunling; Liu, Pi; You, Chun; Lin, Jianping; Zhu, Zhiguang
Graphical abstract: Highlights: A hybrid CO2 electroreduction system mediated by formate dehydrogenase and Cu nanoparticles was constructed. Cu nanoparticles was electrodeposited for cofactor regeneration and as the matrix for enzyme immobilization. The cofactor was tethered with the formate dehydrogenase through a polymer swing arm. Abstract: With the widespread concerns on CO2 capture and utilization, various approaches have been developed to convert CO2 into valuable products. To achieve fast and efficient conversion, a hybrid CO2 electroreduction system was constructed, in which a cofactor-dependent formate dehydrogenase (FDH) was responsible for CO2 enzymatic reduction to formate and Cu nanoparticles (CuNPs) was used for enzyme immobilization and cofactor regeneration. A polyethylene glycol swing arm was further adopted to construct an enzyme-cofactor conjugate and promote the overall reaction. This electron-mediator-free hybrid system containing immobilized FDH-cofactor conjugates and CuNPs achieved a formate production of 8.5 mM and a productivity as high as 11.8 μM mU −1 h −1 with a faraday efficiency of 22.8%, several folds better than systems with unconjugated FDHs alone or with unconjugated FDHs and CuNPs. These results suggest that such hybrid systems may represent a potentially viable alternative for many cofactor-dependent bioelectrochemical applications.